1995
DOI: 10.1002/j.1552-4604.1995.tb04741.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Pharmacokinetics, Safety, and Tolerance of Linopirdine (DuP 996) in Healthy Young Adults and Elderly Volunteers

Abstract: The pharmacokinetics, safety, and tolerance of linopiridine ([3,3-bis(4-pyridinylmethyl)-1-phenylindolin-2-one]; DuP 996) a potential therapeutic agent for Alzheimer's disease, were assessed in double-blind, placebo-controlled, randomized studies in which single oral doses were given to 64 healthy young or elderly males. Young subjects received escalating doses of 0.5 to 55 mg, whereas elderly subjects were given doses of 20 to 45 mg. Linopirdine plasma and urine samples were quantified after liquid extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…In our study, systemic pressure was unchanged or even decreased at the highest dose of linopirdine. We cannot explain the discrepancy, but our findings concur with reports that linopirdine does not affect blood pressure in humans (Saletu et al, 1989;Pieniaszek et al, 1995).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, systemic pressure was unchanged or even decreased at the highest dose of linopirdine. We cannot explain the discrepancy, but our findings concur with reports that linopirdine does not affect blood pressure in humans (Saletu et al, 1989;Pieniaszek et al, 1995).…”
Section: Discussionsupporting
confidence: 84%
“…It was well tolerated and the most frequent adverse event was headache. Results of electroencephalograms, ECGs, and clinical laboratory evaluations were not affected (Pieniaszek et al, 1995). Another study administering single oral doses of 30 mg linopirdine observed electroencephalography changes suggesting vigilance-improving properties and no abnormalities in ECG or laboratory evaluations, indicating a good tolerability (Saletu et al, 1989).…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that linopirdine was well tolerated in patients and did not appreciably alter measured cardiovascular parameters in human volunteers (Pieniaszek et al, 1995). It was also relatively ineffective as a cognition enhancer in patients with AD (Rockwood et , 1997).…”
Section: Cardiovascular Kv7 Channels As Therapeutic Targetsmentioning
confidence: 99%